2000
DOI: 10.1302/0301-620x.82b8.10716
|View full text |Cite
|
Sign up to set email alerts
|

Tibiofemoral movement 2: the loaded and unloaded living knee studied by MRI

Abstract: In 13 unloaded living knees we confirmed the findings previously obtained in the unloaded cadaver knee during flexion and external rotation/internal rotation using MRI. In seven loaded living knees with the subjects squatting, the relative tibiofemoral movements were similar to those in the unloaded knee except that the medial femoral condyle tended to move about 4 mm forwards with flexion. Four of the seven loaded knees were studied during flexion in external and internal rotation. As predicted, flexion (squa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
87
3
6

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(113 citation statements)
references
References 7 publications
17
87
3
6
Order By: Relevance
“…This is supported with findings from fluoroscopy, studies using in vitro analyses, and those using external markers associated with gait laboratory systems [1, 2, 4, 8-10, 12, 13, 16, 18, 19, 21, 22, 24, 25, 34-37]. With increasing knee flexion, the normal knee reportedly experiences more posterior motion of the lateral condyle leading to internal rotation of the tibia with respect to the femur [18,22,25]. In contrast to the normal knee, in vivo kinematic analyses suggest subjects undergoing TKA often experience a motion pattern opposite the normal knee where the condyles slide in the anterior direction with increasing knee flexion [2,8,9,24,28,31,[34][35][36][37].…”
Section: Introductionsupporting
confidence: 70%
“…This is supported with findings from fluoroscopy, studies using in vitro analyses, and those using external markers associated with gait laboratory systems [1, 2, 4, 8-10, 12, 13, 16, 18, 19, 21, 22, 24, 25, 34-37]. With increasing knee flexion, the normal knee reportedly experiences more posterior motion of the lateral condyle leading to internal rotation of the tibia with respect to the femur [18,22,25]. In contrast to the normal knee, in vivo kinematic analyses suggest subjects undergoing TKA often experience a motion pattern opposite the normal knee where the condyles slide in the anterior direction with increasing knee flexion [2,8,9,24,28,31,[34][35][36][37].…”
Section: Introductionsupporting
confidence: 70%
“…Relative tibiofemoral motions medially and laterally were found to be markedly different, as previously described [9,10,13,14]. The medial femoral condyles were found to have less relative movement on the tibias and anteroposterior roll back from extension to 120°of flexion compared with the lateral compartments.…”
Section: Discussionsupporting
confidence: 55%
“…Another study [23] found lateral-but not medial-pivot motion, which we observed in our control group. Hill et al [8] and others [14] observed anterior translation of the medial condyle of 4 mm in 90°, which was slightly more than the findings by Johal et al [10].…”
Section: Discussionmentioning
confidence: 71%